Recognizing Usages of Trade: A Case Study from Electronic Commerce - David McGowan (Washington University Journal of Law & Policy, 2002)
Part I of this Essay briefly discusses the usage of trade concept. Part II discusses the shift in judicial approaches to shrinkwrap licenses from Step-Saver to Mortenson. Part III discusses the lessons of these cases in considering the judicial role in recognizing usages of trade. Part III also considers the warranty of non-infringement and the possibility of disclaiming it by trade usage as an example of the type of analysis courts should engage in when considering usages in the future.
Keywords: Software license agreements; Offer & amp; acceptance (Contracts); Electronic commerce; Usages of trade